Characterization of Pythium Species Associated With Greenhouse Floriculture Crops in Michigan - Munera, Jd (Munera, Johanna Del Castillo); Hausbeck, Mk (Hausbeck, Mary K.)
Michigan ranks third in the United States for the wholesale value of floriculture products, with an estimated value of
Keywords: CYTOCHROME-OXIDASE-II; DAMPING-OFF; BIOLOGICAL-CONTROL; PHYLOGENETIC-RELATIONSHIPS; TRICHODERMA-HARZIANUM; PHYTOPHTHORA-CAPSICI; PLANT-DISEASES; NORTH-CAROLINA; SENSITIVITY; IDENTIFICATION